Transition metal di-chalcogenides and their nanocomposite prospective field emitters - Khare, Ruchita T.; More, Mahendra A.; Late, Dattatray J. (2015 28TH International Vacuum Nanoelectronics Conference (IVNC), 2015)
Layered structured transition metal di-chalcogenides has attracted researchers as a substitute of graphene and its forms for various applications. In an attempt to explore field emission properties of these graphene analogues, synthesis and field emission behaviour of a few layered transition metal di-chalcogenides (TMDs) VS2, MoS2, MoO3 have been investigated at a base pressure of 1x 10(-8) mbar. Furthermore, to improve the field emission properties, composites with RGO and respective oxides were synthesized and compared with the pristine ones. The TMDs and their composites is synthesized employing hydrothermal synthesis route. The preliminary results show that these TMD's and their composites, when synthesized in a controlled manner, can serve as potential field emitters for future field emission based devices.